Invited: Caching in Automated Data Centric Vehicles for Edge Computing Scenarios - Sperling, Nora; Bendrick, Alex; Stohrmann, Dominik; Ernst, Rolf (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
With the current trend towards large data volumes, state-of-the-art communication and data management solutions based on the publish/subscribe pattern reach the network limits, hampering the deployment of advanced edge and cloud computing services. A main reason is the established publisher-centric distribution mechanism that over-utilizes network resources. We suggest a network and subscriber-centric adaptive data caching communication scheme supported by dynamic network management and configuration, which has great potential to solve the data distribution challenges. We show that state-of-the-art publish/subscribe middlewares like Data Distribution Service (DDS) can transparently be combined with such software caching.